Rasburicase-induced Methemoglobinemia: A Case Report and Literature Review. Issue 6 (August 2021) - Pirrone, Ilaria; Farruggia, Piero; Cacciatore, Francesca; Giambona, Antonino; Guarina, Angela; Marcello, Anna Paola; Mosa, Clara; Scalzo, Simona; D'Angelo, Paolo
Abstract : Rasburicase is a recombinant urate oxidase enzyme indicated for tumor lysis syndrome, a potential life-threatening oncologic emergency that occurs most commonly during initial chemotherapy for hematological malignancies. As a result of the defects in the physiological antioxidant pathway, erythrocytes of patients with glucose-6-phosphate dehydrogenase deficiency are not protected against the oxidizing stress exerted by hydrogen peroxide generated with the administration of rasburicase. The authors report a 14-year-old patient, diagnosed with T-cell acute lymphoblastic leukemia, who developed methemoglobinemia and hemolytic anemia with low oxygen saturation after starting steroids, hyperhydratation, and rasburicase administration. The complications resolved with supportive therapy only.